Rama of golden age : an epic of India - Watson, Jane Werner, 1915-; Frame, Paul, 1913-; Valmiki. Ramayana (Champaign, Ill. : Garrard Publising Company, 1971)
A prose retelling of India's epic poem describing the good prince Rama's triumph over the evil demon king, Ravana.